2010
DOI: 10.1016/j.ccr.2009.11.023
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 Is a Mitochondria-Localized Tumor Suppressor Required for Maintenance of Mitochondrial Integrity and Metabolism during Stress

Abstract: SUMMARY The sirtuin gene family (SIRT) is hypothesized to regulate the aging process and play a role in cellular repair. This work demonstrates that SIRT3−/− mouse embryonic fibroblasts (MEFs) exhibit abnormal mitochondrial physiology as well as increases in stress-induced superoxide levels and genomic instability. Expression of a single oncogene (Myc or Ras) in SIRT3−/− MEFs results in in vitro transformation and altered intracellular metabolism. Superoxide dismutase prevents transformation by a single oncoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
790
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 720 publications
(840 citation statements)
references
References 34 publications
(44 reference statements)
46
790
3
1
Order By: Relevance
“…Furthermore, SIRT3 is the major deacetylase in the mitochondrion (99). SIRT3 deacetylates FOXO3a, which strengthens the DNA-binding of FOXO3a, but does not change the mitochondrial location of FOXO3a (100). It has been demonstrated that FOXO3a forms a complex with SIRT3 and mitochondrial RNA polymerase, binding to mitochondrial DNA, and further increasing the expression of oxidative phosphorylation-associated proteins, ultimately, increasing mitochondrial respiration (59).…”
Section: Acetylation Of Foxo Proteinsmentioning
confidence: 99%
“…Furthermore, SIRT3 is the major deacetylase in the mitochondrion (99). SIRT3 deacetylates FOXO3a, which strengthens the DNA-binding of FOXO3a, but does not change the mitochondrial location of FOXO3a (100). It has been demonstrated that FOXO3a forms a complex with SIRT3 and mitochondrial RNA polymerase, binding to mitochondrial DNA, and further increasing the expression of oxidative phosphorylation-associated proteins, ultimately, increasing mitochondrial respiration (59).…”
Section: Acetylation Of Foxo Proteinsmentioning
confidence: 99%
“…It regulates mitochondrial activity by ROS in many cell types and modulates CREB phosphorylation and fat metabolism (Shi et al ., 2005; Hirschey et al ., 2010; Kim et al ., 2010). Importantly, SIRT3 has an essential role in enhancing the mitochondrial antioxidant glutathione, which could contribute to reduce aging in mammals (Someya et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…SIRT3 is a soluble mitochondrial protein highly expressed in mitochondrial rich tissues and also plays critical roles related to tumor suppression, cellular stress, fat acid metabolism, oxidative stress response, and age-associated hearing loss (Hirschey et al, 2010;Kim et al, 2010;Someya et al, 2010). Lombard et al (2007) found that no abnormalities were identified in SIRT3-deficient mice under non-stress conditions; however, the hyperacetylation of mitochondrial proteins was observed when stress was applied.…”
Section: Characteristics and Functions Of Sirt3mentioning
confidence: 99%
“…Fortunately, SIRT3 has been demonstrated to participate in numerous biological processes including anti-oxidation reactions, cell survival, and mitochondrial protection, all of which could contribute to the treatment of ischemic heart disease (Kim et al, 2010;Someya et al, 2010;Dittenhafer-Reed et al, 2015). Since loss of cardiomyocytes due to cell death is the main cause of cardiac dysfunction following MI, inhibition of apoptosis or necrosis is a critical necessity.…”
Section: Role Of Sirt3 In Attenuating Ischemia And/or Reperfusion-indmentioning
confidence: 99%